Management Of Biology Laboratory Administration At SMA N 7 Bengkulu Utara - Septiana Septiana; Suyatno Suyatno; Dian Hidayati (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Purpose-Laboratories play a crucial role in supporting science learning in senior high schools by facilitating practical activities that enhance students’ scientific skills, critical thinking, and conceptual understanding. This study aims to describe the management of a biology laboratory at SMA Negeri 7 Bengkulu Utara and to identify challenges encountered in its implementation. Design/methods/approach-This study employed a qualitative descriptive approach. Data were collected through semi-structured interviews with biology teachers and the head of the biology laboratory. The data were analyzed based on management functions, including planning, organizing, implementation, supervision, and evaluation. Findings-The findings indicate that biology laboratory management has been implemented in accordance with basic management functions. However, its implementation has not been optimal. Planning and practical activities are constrained by limited laboratory equipment, materials, budget allocation, availability of laboratory personnel, and restricted instructional time. In addition, laboratory evaluation has not been conducted systematically or supported by standardized assessment instruments. Research implications/limitations-This study is limited to a single school context and relies solely on interview data, which may affect the generalizability of the findings. Nevertheless, the results provide practical insights for schools and education stakeholders to improve biology laboratory management, particularly in optimizing existing resources and strengthening systematic evaluation practices.